Pengaruh Model Pembelajaran Berbasis Lingkungan terhadap Hasil Belajar Siswa Tentang Pertumbuhan Hewan pada Tema 1 Subtema 3 Kelas 3 SD Percontohan 091317 - Haposan Pasaribu; Lisbet N. Sihombing; Eva Pasaribu (Medan Resource Center, 2022)
This research was motivated by the low average value of learning outcomes because students did not understand the concepts taught by the teacher by rote. So that learning seems boring. Besides that, teachers also use the environment less as a learning resource. The purpose of this study was to find out whether there is an effect of environmental-based learning on student learning outcomes about animal growth on theme 1 sub-theme 3 Class III Pilot Elementary School 091317. The type of research in writing this thesis is field research with a correlational quantitative approach. The Data Collection Techniques Used Are Observation, Test, And Documentation. The data analysis technique used is the t-test formula. From the results of the study, it is known that the value of learning outcomes in the control class obtained an average value of 4.09. With the highest score of 80 and the lowest score of 65. Meanwhile, in the experimental class, the average score was 41.5. With the highest score of 90 and the lowest score of 65. Thus, it can be concluded that there is an effect of environmental-based learning on learning outcomes about animal growth in theme 1 sub-theme 3 class III pilot elementary school. This can be seen from the analysis of the data obtained with a T-value of 4.183 with a significance of 0.000usingUsing T Table of 2.1. Based on these data, T Count 1.268 > T Table 1.419 and significance 0.000 < 0.00.